Anti-dazzle polyvinyl alcohol film, preparation method thereof and polaroid

By adding shell microspheres combined with hydrophilic nanoparticles and organic microspheres to the PVA film as anti-glare particles, the problem that the existing polarizer anti-glare function is susceptible to external influences is solved, and an efficient and uniform anti-glare effect is achieved, and the preparation cost is reduced.

CN119798896AActive Publication Date: 2025-04-11ANHUI WANWEI ADVANCED FUNCTIONAL MEMBRANE MATERIALS RES INST CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510301620.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

The anti-glare function of existing polarizers mainly depends on the coating of the TAC layer, which is susceptible to external physical factors, and lacks adhesion in high temperature and high humidity environments, resulting in uneven optical performance at the perspective angle and increasing manufacturing costs.

Method used

The non-coated anti-glare function is achieved by adding shell microspheres with hydrophilic nanoparticles combined with organic microspheres to the polyvinyl alcohol (PVA) film. The anti-glare particles are uniformly dispersed in the PVA resin, and use the refractive and reflective effects of light to enhance the scattering effect of light, thereby reducing glare.

Benefits of technology

It is achieved without increasing the thickness, improve the anti-glare performance of the polarizer, enhance the optical uniformity and transmissibility, reduce the preparation cost, and improve the weather resistance and durability of the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798896A_ABST
    Figure CN119798896A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-dazzle polyvinyl alcohol film as well as a preparation method and application thereof, and relates to the technical field of polyvinyl alcohol films, the polyvinyl alcohol film comprises the following components in parts by weight: 80-90 parts of PVA resin, 8-10 parts of a plasticizer, 0.1-0.5 part of a surfactant, 0.5-1 part of an antioxidant, 0.5-1 part of an ultraviolet absorbent and 0.1-1.5 parts of anti-dazzle particles; wherein the anti-dazzle particles are shell layer microspheres formed by combining hydrophilic nano particles and hydrophilic organic microspheres; the anti-dazzle function of the polaroid is achieved by adding the anti-dazzle functional particles into the polyvinyl alcohol film, meanwhile, the optical performance such as the polarization degree and the transmittance of the polyvinyl alcohol film subjected to iodine dyeing stretching is not affected, and compared with a conventional polaroid achieving anti-dazzle through a TAC layer, the prepared polaroid is better in anti-dazzle optical uniformity, the anti-dazzle effect is better, and the anti-dazzle effect is better. And meanwhile, the problem of non-uniform display optics caused by damage of the TAC anti-dazzle coating does not exist, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl alcohol films, and in particular to an anti-glare polyvinyl alcohol film and a preparation method thereof, and a polarizer. Background Art

[0002] Polarizer is an indispensable optical component in liquid crystal displays (LCDs) and other optoelectronic devices. Its basic composition is composed of polyvinyl alcohol (PVA) film and two layers of triacetyl cellulose (TAC) film. The PVA film plays the core polarization function, while the TAC film mainly plays a protective and supporting role. In addition, the surface of the TAC film generally has multiple layers of coating to give it diversified functions, such as anti-reflection, anti-glare and other functions. The function of the anti-glare film can further improve the display quality of the screen, especially in strong light or direct sunlight, it can effectively reduce glare, improve display effects and visual comfort, and achieve high performance and high competitiveness of the product.

[0003] Glare refers to a visual condition that causes visual discomfort or reduces the visibility of objects due to inappropriate brightness distribution in the field of vision or extreme brightness contrast in space and time. It is mainly caused by strong light reflecting on the surface. Anti-glare film can reduce light reflection. When light hits the anti-glare film, the film material will change the propagation path of the light, and the intensity of the reflected light will be reduced, thereby reducing the intensity of glare.

[0004] At present, the anti-glare function of polarizers on the market and in patents is mainly achieved by the TAC layer, which is prepared by mixing light scattering particles with adhesive resin and coating them on the TAC surface layer. However, this method has some disadvantages, such as the anti-glare coating is usually thin and easily affected by external physical factors, such as scratches and wear, which may cause the coating to lose its anti-glare effect and affect the visual quality. In high temperature and high humidity environments, the adhesion of the anti-glare coating may be insufficient, and it is easy to peel or bubble, affecting the uniformity and consistency of the coating, resulting in insufficient optical performance under the viewing angle, color difference or uneven brightness. At the same time, with the development trend of thinning polarizers, whether the anti-glare function can be achieved without coating, so as to achieve the purpose of reducing thickness, is the result that polarizer companies are currently pursuing; on the other hand, with the development of new displays, the polarizer TAC layer is gradually required to have multiple functions at the same time, such as anti-fouling performance, anti-static performance, chemical resistance, scratch resistance, anti-glare, anti-reflection and other functions, and the addition of each function will greatly increase the TAC manufacturing cost, which is the main obstacle to reducing the cost of polarizers. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-glare polyvinyl alcohol film and a preparation method thereof and a polarizer to solve the following technical problems: How to achieve anti-glare function in other layers without coating.

[0006] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present invention discloses an anti-glare polyvinyl alcohol film, which comprises the following components in parts by weight: 80-90 parts of PVA resin, 8-10 parts of plasticizer, 0.1-0.5 parts of surfactant, 0.5-1 parts of antioxidant, 0.5-1 parts of ultraviolet absorber, and 0.1-1.5 parts of anti-glare particles; Among them, the anti-glare particles are shell microspheres that are a combination of hydrophilic nanoparticles and hydrophilic organic microspheres, and the mass fraction of the hydrophilic nanoparticles in the shell microspheres is 1-10%; the surface of the shell microspheres contains hydrophilic groups such as hydroxyl, carboxyl, and amino, so that they have good compatibility and dispersibility in the casting solution.

[0007] Furthermore, the hydrophilic nanoparticles are a combination of any one or more of silicon dioxide nanoparticles, titanium dioxide nanoparticles, zirconium dioxide nanoparticles, and aluminum oxide nanoparticles, and the nanoparticles are prepared by a sol-gel method.

[0008] Furthermore, the hydrophilic organic microspheres are any one or more combinations of polyvinyl alcohol-based microspheres, polymethyl methacrylate-based microspheres and polystyrene-based microspheres.

[0009] Furthermore, the method for preparing the shell microspheres comprises the following steps: Step 1, preparing hydrophilic nanoparticles with positive charges on the surface; The precursor solution and dispersant of the hydrophilic nanoparticles are added into a mixed solvent of ethanol and ammonia water, and then hydrolyzed at a hydrolysis temperature, and finally centrifugally vacuum dried to obtain hydrophilic nanoparticles with positive charges on the surface; Taking silica nanoparticles as an example, the preparation process is as follows: a certain amount of tetraethyl silicate and vinyl triethoxysilane are added to a mixed solvent of ammonia water and ethanol, and then hydrolyzed at 40°C for 1 hour and then aged for 24 hours, and finally centrifuged and vacuum dried for 24 hours to obtain nano silica particles with a particle size of 10-30nm and a positively charged surface; Step 2: preparing hydrophilic organic microspheres with negative charges on the surface; The hydrophilic organic microspheres are dispersed in a sodium hydroxide solution to partially deprotonate the hydrophilic groups, and then centrifugally dried to obtain the hydrophilic organic microspheres with negative charges on the surface.

[0010] Taking polyvinyl alcohol microspheres as an example, the preparation process is as follows: a certain amount of polyvinyl alcohol microspheres are immersed in a 0.1 mol / L sodium hydroxide solution, stirred at room temperature for 12-24 hours, and centrifuged and dried to obtain polyvinyl alcohol microspheres with negative charges on the surface; Step 3: Add hydrophilic nanoparticles with positive charges on the surface and hydrophilic organic microspheres with negative charges on the surface into ethanol solvent in proportion, mix for 15-20 hours, and then centrifuge and dry to obtain shell microspheres.

[0011] Furthermore, the difference in refractive index between the shell microspheres and the PVA resin is 0.01-0.1. If the difference is too high, the haze of the film will be significantly increased, but the transmittance of the film will be greatly reduced. If the difference is small, the effect of improving the haze of the film will be relatively weak; and the difference in refractive index between the hydrophilic nanoparticles and the hydrophilic organic microspheres in the shell microspheres is 0.01-0.1. This difference can make the scattering effect of light after multiple refractions and reflections better, and the Mie scattering of light after passing through the hydrophilic organic microspheres and the Rayleigh scattering of light after passing through the hydrophilic nanoparticles can enhance the uniformity and transmittance of the light, thereby improving the high transmittance and high haze performance of the film.

[0012] Furthermore, the average particle size of the shell microspheres is ≤5 μm, so as to avoid the particle size being too large and causing the particle shell microspheres to be blocked by the filter and lost.

[0013] When the weight of the PVA resin is 80-90 parts, the weight of the anti-glare particles is strictly controlled at 0.1-1.5 parts. This is because, if the content of the anti-glare particles is too high, the haze of the film will increase, and it will easily cause the anti-glare particles to agglomerate, and it will weaken the complexation of the PVA molecular chain with iodine, affecting the optical properties of the anti-glare polyvinyl alcohol film and the prepared polarizer; if the content is too low, the anti-glare effect cannot be effectively produced.

[0014] Furthermore, the polymerization degree of the PVA resin is 2000-4000. This is because too high a polymerization degree will lead to uneven dispersion of the additive and poor color uniformity of the prepared film; too low a polymerization degree will lead to poor mechanical tensile properties of the optical film and easy film breakage.

[0015] Furthermore, the alcoholysis degree of the PVA resin is 98-99.9%, preferably 99-99.9%. This is because, if the alcoholysis degree is too low, the hydrogen bond network stability of the prepared PVA polarizer will be worse, and the film shrinkage will be worse under high temperature and high humidity. In addition, if the alcoholysis degree is too low, PVA will easily absorb water under high temperature and high humidity, and the weather resistance of the polarizer will deteriorate.

[0016] Furthermore, the plasticizer is a combination of any one or more of glycerol, diglycerol, polyglycerol, ethylene glycol and propylene glycol.

[0017] Furthermore, the surfactant is a composition of at least two surfactants selected from the group consisting of nonionic surfactants and / or anionic surfactants, wherein the nonionic surfactants include alkyl esters such as polyoxyethylene lauryl ester, alkyl amines such as polyoxyethylene lauryl amino ester, and alkyl amide surfactants such as polyoxyethylene lauric acid amide; and the anionic surfactants include alkyl sulfonates, sodium dodecyl sulfate, sodium dodecyl sulfite, benzene sulfonates, and alkyl carboxylates.

[0018] Furthermore, the antioxidant is a combination of any one or more of butylated hydroxytoluene, phosphite, phosphate, thiodipropionate, and sodium bisulfite.

[0019] Furthermore, the ultraviolet absorber is a combination of any one or more of benzotriazoles, benzophenones, triazines, and benzoates.

[0020] In a second aspect, the present invention discloses a method for preparing the anti-glare polyvinyl alcohol film as described above, comprising the following steps: S1. Add PVA resin, plasticizer, surfactant, antioxidant, UV absorber and anti-glare particles to the solvent in proportion by weight, heat to 130-170°C and stir for 2-10h, preferably 145-160°C and stir for 4-7h to obtain a casting solution with a solute mass fraction of 20-40%; S2. Send the film casting stock solution into the extruder for degassing. The extruder head pressure is 1.0-2.0MPa, the middle section temperature is 100-150℃, and the G / P inlet pump pressure is 2.0-5.0MPa. If the pressure is too low, the degassing effect is poor, and if the pressure is too high, the equipment load is too large. S3. The degassing film casting stock solution is filtered with a disc filter with a filter aperture of 10-20um; if the filter aperture is too large, the impurity gel cannot be removed; if the aperture is too small, the pressure drop is too large, the power load of the equipment increases, and some anti-glare particles will also be filtered.

[0021] S4, the filtered film casting stock solution is cast onto the casting roller through the slit die to form a liquid film. The diameter, linear speed, temperature, wind field, extruder feed rate and die cross-sectional area of ​​the casting roller should be matched to reduce the water content of the liquid film to 18-35%, preferably 22-28%. At this time, if the water content of the liquid film is controlled too high, it will be difficult to peel off, and the load of the subsequent pre-drying stage will increase; if the water content of the liquid film is controlled too low, the equipment load will be too large and the productivity will decrease; then the water content is reduced to 5-15% through pre-drying. At this time, the water content is too low, which is not conducive to the formation of uniform and dense PVA The crystal network, the stability of the prepared PVA polarizer crystal and the chemical cross-linking network deteriorate, and the mechanical properties deteriorate; too high water content is not conducive to the subsequent heat treatment process, and problems such as water droplets and glycerin are prone to occur; the water content is then reduced to 0.1-5%, preferably 1.5-3.5% by heat treatment. At this time, the water content is too low and it is easy to cause difficulty in dyeing during the polarizer processing process; too high water content will cause slow changes in the crystal structure of PVA during storage, shorten the shelf life, and easily increase the amount of PVA dissolution during production; finally, the anti-glare polyvinyl alcohol film is rolled up.

[0022] Furthermore, in step S4, the heat treatment stage can be performed in one or more stages, preferably in a multi-stage manner, and the temperature of each stage tends to first increase and then decrease along the production direction.

[0023] Furthermore, the temperature of the highest section of the heat treatment is reduced by 5-10°C, and the linear speed of the heat treatment guide roller is reduced by 0.5-1m / min to extend the heat treatment time; because lower temperature heat treatment can keep the film with a smaller grain size, and a smaller grain size is beneficial to improving the light transmittance of the film, and longer heat treatment time helps to release residual stress, reduce internal stress, and improve film ductility and toughness.

[0024] Furthermore, the solvent is water or dimethyl sulfoxide.

[0025] Furthermore, the anti-glare polyvinyl alcohol film has a light transmittance of ≥85% and a haze of 2-50%.

[0026] In a third aspect, the present invention further discloses a polarizer, the intermediate film of which is a polarizer film made by iodine-dyed and stretched anti-glare polyvinyl alcohol film as described above, and the glossiness of the polarizer film at an angle of 60° is 30-70GU, so that it has excellent anti-glare performance without affecting its optical performance.

[0027] Beneficial effects of the present invention: (1) During the preparation process of the anti-glare polyvinyl alcohol film of the present invention, anti-glare functional particles are added to the polyvinyl alcohol film to achieve the anti-glare function of the polarizer, while the optical properties of the polyvinyl alcohol film after iodine dyeing and stretching, such as polarization degree and transmittance, are not affected. Compared with the conventional polarizer that relies on the TAC layer to achieve anti-glare, the prepared polarizer has better anti-glare optical uniformity because the anti-glare particles are evenly dispersed in the PVA optical film. At the same time, there is no problem of display optical non-uniformity caused by damage to the TAC anti-glare coating. At the same time, the preparation process is saved, the preparation process is simplified, and an anti-glare polyvinyl alcohol film with stronger optical properties is obtained.

[0028] (2) The present invention realizes the anti-glare function in the PVA optical film layer, which can reduce the functions that need to be realized by the TAC layer, reduce the raw material cost and operating cost of the polarizer, and make the product more competitive in the market. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described below in conjunction with the accompanying drawings.

[0030] Figure 1 is a SEM image of nano-silicon dioxide with positive charges on the surface in Example 1 of the present invention; Figure 2 is a SEM image of the polyvinyl alcohol microspheres with negative charges on the surface in Example 1 of the present invention; Figure 3 is a SEM image of the shell microspheres in Example 1 of the present invention; Figure 4 is a SEM image of the anti-glare polyvinyl alcohol film in Example 2 of the present invention; Figure 5 This is the EDS energy spectrum of the anti-glare polyvinyl alcohol film in Example 2 of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0033] Example 1 Preparation of anti-glare particles: Step 1: 100 g of tetraethyl silicate and 10 g of vinyl triethoxysilane were mixed with a mixed solvent of 2500 g of ethanol and 150 g of ammonia water, and then hydrolyzed at 40°C for 1 h and aged for 24 h, and finally vacuum dried for 12-24 h to obtain nano-silicon dioxide with a positive charge on the surface. The prepared nanoparticles were observed by electron microscopy to obtain the following: Figure 1 The SEM image shown shows that the particle size is 10-50 nm; Step 2: Disperse 100 g of polyvinyl alcohol microspheres in a 0.1 mol / L sodium hydroxide solution, stir at room temperature for 24 h, and then centrifuge and dry to obtain polyvinyl alcohol microspheres with negative surface charges. Observe the prepared microspheres under an electron microscope to obtain the following: Figure 2 The SEM image shown shows that the particle size is ≤5um; Step 3: 5 g of nano-silica with positive surface charge and 95 g of polyvinyl alcohol microspheres with negative surface charge were added to 300 mL of ethanol solvent, mixed for 15-20 hours, and then centrifuged and dried to obtain shell microspheres. The prepared shell microspheres were observed by point-in observation, and the following results were obtained: Figure 3 As shown in the SEM image, the particle size is ≤5um, and the nanoparticles are well dispersed on the surface of the microspheres.

[0034] Example 2 Preparation of anti-glare polyvinyl alcohol film: 850g PVA resin, 90g glycerol, 3g sodium dodecylbenzene sulfonate, 8g butylhydroxytoluene, 7g methyl benzoate, and 10g anti-glare particles prepared in Example 1 were added to 2259g water in sequence, heated to 150°C and stirred for 6h to obtain a casting solution with a solute mass fraction of 30%; the casting solution was sent to an extruder for degassing, the extruder head pressure was 1.5MPa, the middle section temperature was 130°C, and the G / P inlet pump pressure was 3.5MPa; the degassed casting solution was filtered using a disc filter with a filtration aperture of 15um; the filtered casting solution was cast onto a casting roller through a slit die to form a liquid film, so that the water content of the liquid film was reduced to 25%, and then the water content was reduced to 12% by pre-drying, and then the water content was reduced to 3% by heat treatment, and finally the anti-glare polyvinyl alcohol film was rolled up, and the prepared anti-glare polyvinyl alcohol film was sampled for electron microscopy observation, and the following was obtained: Figure 4 The SEM images shown and Figure 5 From the corresponding EDS energy spectrum shown, it can be found that the anti-glare particles are well dispersed in the PVA matrix and no agglomeration occurs.

[0035] Example 3 Preparation of anti-glare polyvinyl alcohol film: 800g PVA resin, 80g glycerol, 1g sodium dodecylbenzene sulfonate, 5g butylhydroxytoluene, 5g methyl benzoate, and 1g anti-glare particles prepared in Example 1 were added to 3568g dimethyl sulfoxide solvent in sequence, heated to 145°C and stirred for 7h to obtain a casting solution with a solute mass fraction of 20%; the casting solution was sent to an extruder for degassing, the extruder head pressure was 1.0MPa, the middle section temperature was 100°C, and the G / P inlet pump pressure was 2.0MPa; the degassed casting solution was filtered using a disc filter with a filtration pore size of 10um; the filtered casting solution was cast through a slit die onto a casting roller to form a liquid film, so that the water content of the liquid film was reduced to 18%, and then the water content was reduced to 5% by pre-drying, and then the water content was reduced to 1% by heat treatment, and finally the anti-glare polyvinyl alcohol film was rolled up.

[0036] Example 4 Preparation of anti-glare polyvinyl alcohol film: 900g PVA resin, 100g glycerol, 5g sodium dodecylbenzene sulfonate, 10g butylhydroxytoluene, 10g methyl benzoate, and 15g anti-glare particles prepared in Example 1 were added to 1560g dimethyl sulfoxide solvent in sequence, heated to 160°C and stirred for 4h to obtain a casting solution with a solute mass fraction of 40%; the casting solution was sent to an extruder for degassing, the extruder head pressure was 2.0MPa, the middle section temperature was 150°C, and the G / P inlet pump pressure was 5.0MPa; the degassed casting solution was filtered using a disc filter with a filtration aperture of 20um; the filtered casting solution was cast through a slit die to a casting roller to form a liquid film, so that the water content of the liquid film was reduced to 35%, and then the water content was reduced to 15% by pre-drying, and then the water content was reduced to 5% by heat treatment, and finally the anti-glare polyvinyl alcohol film was rolled up.

[0037] Example 5 Preparation of anti-glare polyvinyl alcohol film: 850g PVA resin, 90g ethylene glycol, 3g potassium laurate, 8g phosphite, 7g methyl benzoate, and 10g anti-glare particles prepared in Example 1 were added to 2259g water in sequence, heated to 150°C and stirred for 6h to obtain a casting solution with a solute mass fraction of 30%; the casting solution was sent to an extruder for degassing, the extruder head pressure was 1.5MPa, the middle section temperature was 120°C, and the G / P inlet pump pressure was 3.5MPa; the degassed casting solution was filtered using a disc filter with a filtration aperture of 15um; the filtered casting solution was cast through a slit die onto a casting roller to form a liquid film, so that the water content of the liquid film was reduced to 25%, and then the water content was reduced to 12% by pre-drying, and then the water content was reduced to 3% by heat treatment, and finally the anti-glare polyvinyl alcohol film was rolled up.

[0038] Example 6 Preparation of anti-glare polyvinyl alcohol film: 850g PVA resin, 90g diglycerol, 3g polyoxyethylene lauryl amino ester, 8g thiodipropionate, 7g methyl 3,4,5-trimethoxybenzoate, and 10g anti-glare particles prepared in Example 1 were added to 2259g dimethyl sulfoxide solvent in sequence, heated to 150°C and stirred for 6h to obtain a casting solution with a solute mass fraction of 30%; the casting solution was sent to an extruder for degassing, the extruder head pressure was 1.5MPa, the middle section temperature was 130°C, and the G / P inlet pump pressure was 3.5MPa; the degassed casting solution was filtered using a disc filter with a filtration aperture of 15um; the filtered casting solution was cast through a slit die to a casting roller to form a liquid film, so that the water content of the liquid film was reduced to 25%, and then the water content was reduced to 12% by pre-drying, and then the water content was reduced to 3% by heat treatment, and finally the anti-glare polyvinyl alcohol film was rolled up.

[0039] Comparative Example 1 Preparation of anti-glare polyvinyl alcohol film: 850g PVA resin, 90g glycerol, 3g sodium dodecylbenzene sulfonate, 8g butylhydroxytoluene, and 7g methyl benzoate were added to 2259g water, heated to 150°C and stirred for 6h to obtain a casting solution; the casting solution was sent to an extruder for degassing, the extruder head pressure was 1.5MPa, the middle section temperature was 120°C, and the G / P inlet pump pressure was 3.5MPa; the degassed casting solution was filtered using a disc filter with a filtration aperture of 15um; the filtered casting solution was cast onto a casting roller through a slit die to form a liquid film, so that the water content of the liquid film was reduced to 25%, and then the water content was reduced to 12% by pre-drying, and then the water content was reduced to 3% by heat treatment, and finally the polyvinyl alcohol film was rolled up; then a TAC film with an anti-glare coating on the market was bonded to one side of the polyvinyl alcohol film by PVA water glue, wherein the haze of the anti-glare TAC film was the same as that of the anti-glare polyvinyl alcohol film in Example 2.

[0040] Comparative Example 2 Compared with Comparative Example 1, the only difference is that the TAC film bonded has no anti-glare coating, and the other steps and conditions are exactly the same.

[0041] Comparative Example 3 Compared with Example 2, the only difference is that the anti-glare particles prepared in Example 1 are not added, and the other steps and conditions are exactly the same, and finally a polyvinyl alcohol film is prepared.

[0042] Comparative Example 4 Preparation of anti-glare polyvinyl alcohol film: Compared with Example 2, the only difference is that the amount of anti-glare particles prepared in Example 1 is increased from 10 g to 20 g, and the other steps and conditions are exactly the same, and finally an anti-glare polyvinyl alcohol film is prepared.

[0043] Comparative Example 5 Compared with Example 2, the only difference is that the amount of anti-glare particles prepared in Example 1 is reduced from 10 g to 0.5 g, and the other steps and conditions are exactly the same, and finally an anti-glare polyvinyl alcohol film is prepared.

[0044] Comparative Example 6 Compared with Example 2, the only difference is that the anti-glare particles are replaced by the nano-silicon dioxide prepared in Example 1, and the other steps and conditions are exactly the same, and finally an anti-glare polyvinyl alcohol film is prepared.

[0045] Comparative Example 7 Compared with Example 2, the only difference is that the anti-glare particles are replaced by the polyvinyl alcohol microspheres prepared in Example 1, and the other steps and conditions are exactly the same, and finally an anti-glare polyvinyl alcohol film is prepared.

[0046] The optical properties of the polyvinyl alcohol films prepared in Examples 2-6 and Comparative Examples 1-7 were tested by the following method: Light transmittance: Use a haze meter to test; cut a 5×5cm polyvinyl alcohol film and fix it where the light spot enters. The instrument automatically detects the light transmittance of the film, and tests it multiple times and takes the average; Haze: Use a haze meter to test; cut a 5×5cm polyvinyl alcohol film and fix it where the light spot enters. The instrument automatically detects the haze of the film, and tests it multiple times and takes the average; 60° angle gloss: Use a gloss meter to test; first calibrate the gloss meter, then place the film on a black background, stick the gloss meter on the film surface to directly test its gloss, test multiple times and take the average; Polarization degree after dyeing: detected by phase difference meter polarization mode; Single body transmittance: Detected by phase difference meter polarization mode.

[0047] The test results are listed in Table 1. Table 1 is as follows: Table 1

[0048] right Figure 1 By analyzing the data in Table 1, it can be known that in the anti-glare polyvinyl alcohol film prepared by the preparation method of the present invention in Examples 2-6, the anti-glare particles have good dispersion, the transmittance is ≥85%, the haze is in the range of 2%-50%, and it has stronger optical properties of high transmittance and high haze, and can be applied to the intermediate film (polarizing film) of the polarizer.

[0049] Comparative Example 1 uses the prior art to laminate a TAC film with an anti-glare coating on the polyvinyl alcohol side. Although it has anti-glare performance, its surface coating has poor adhesion and is not scratch-resistant, which easily leads to non-uniform light. Comparative Example 2 uses the prior art to laminate a pure TAC film on the polyvinyl alcohol side, and its anti-glare performance is relatively weak. In Comparative Example 3, no anti-glare particles are added, so the anti-glare performance is poor. In Comparative Example 4, too much anti-glare particles are added, which will affect the dispersibility of the anti-glare particles in the polyvinyl alcohol film. Although its haze is very high, the transmittance is greatly reduced, and the glossiness of the corresponding polarizing film is reduced. It also reduces the complexing ability of the polyvinyl alcohol molecular chain with iodine, affecting the optical properties of the polarizing film such as polarization degree and transmittance. In Comparative Example 5, too little anti-glare particles are added, and the anti-glare effect is weak. In Comparative Example 6, only nano-silica was added as anti-glare particles, and the resulting polyvinyl alcohol film had lower haze and higher gloss. In Comparative Example 7, only polyvinyl alcohol microspheres were added as anti-glare particles. Because their refractive index was close to that of the polyvinyl alcohol matrix, the resulting polyvinyl alcohol film had high light transmittance, but low haze and high gloss.

[0050] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. An anti-glare polyvinyl alcohol film, characterized in that: The composition includes the following components in parts by weight: 80-90 parts of PVA resin, 8-10 parts of plasticizer, 0.1-0.5 parts of surfactant, 0.5-1 parts of antioxidant, 0.5-1 parts of ultraviolet absorber, and 0.1-1.5 parts of anti-glare particles; The anti-glare particles are shell microspheres formed by combining hydrophilic nanoparticles with hydrophilic organic microspheres, and the mass fraction of the hydrophilic nanoparticles in the shell microspheres is 1-10%.

2. The anti-glare polyvinyl alcohol film according to claim 1, characterized in that: The hydrophilic nanoparticles are any one or more combinations of silicon dioxide nanoparticles, titanium dioxide nanoparticles, zirconium dioxide nanoparticles, and aluminum oxide nanoparticles, and the nanoparticles are prepared by a sol-gel method.

3. The anti-glare polyvinyl alcohol film according to claim 2, characterized in that: The hydrophilic organic microspheres are any one or more of polyvinyl alcohol-based microspheres, polymethyl methacrylate-based microspheres and polystyrene-based microspheres.

4. The anti-glare polyvinyl alcohol film according to claim 3, characterized in that: The method for preparing the shell microspheres comprises the following steps: Step 1: adding a precursor solution of hydrophilic nanoparticles and a dispersant into a mixed solvent of ethanol and ammonia water, then hydrolyzing at a hydrolysis temperature, and finally centrifugally vacuum drying to obtain hydrophilic nanoparticles with positive charges on the surface; Step 2: dispersing the hydrophilic organic microspheres in a sodium hydroxide solution to partially deprotonate the hydrophilic groups, and then centrifugally drying to obtain hydrophilic organic microspheres with negative charges on the surface; Step 3: Add hydrophilic nanoparticles with positive charges on the surface and hydrophilic organic microspheres with negative charges on the surface into ethanol solvent in proportion, mix for 15-20 hours, and then centrifuge and dry to obtain shell microspheres.

5. The anti-glare polyvinyl alcohol film according to claim 1, characterized in that: The difference in refractive index between the shell microsphere and the PVA resin is 0.01-0.1, and the difference in refractive index between the hydrophilic nanoparticles and the hydrophilic organic microspheres in the shell microsphere is 0.01-0.

1.

6. The anti-glare polyvinyl alcohol film according to claim 1, characterized in that: The plasticizer is any one or more of glycerol, diglycerol, polyglycerol, ethylene glycol and propylene glycol.

7. The anti-glare polyvinyl alcohol film according to claim 1, characterized in that: The surfactant is a composition of at least two surfactants selected from nonionic surfactants and / or anionic surfactants, wherein the nonionic surfactants include alkyl esters, alkyl amines, and alkyl amides; and the anionic surfactants include alkyl sulfonates, sodium dodecyl sulfate, sodium dodecyl sulfite, benzene sulfonates, and alkyl carboxylates.

8. The anti-glare polyvinyl alcohol film according to claim 1, characterized in that: The antioxidant is any one or more of butylated hydroxytoluene, phosphite, phosphate, thiodipropionate and sodium bisulfite.

9. The anti-glare polyvinyl alcohol film according to claim 1, characterized in that: The ultraviolet absorber is any one or more combinations of benzotriazoles, benzophenones, triazines, and benzoates.

10. A method for preparing an anti-glare polyvinyl alcohol film according to any one of claims 1 to 9, characterized in that: The steps include: S1. Add PVA resin, plasticizer, surfactant, antioxidant, UV absorber and anti-glare particles to the solvent in order according to the weight ratio, heat to 130-170°C and stir for 2-10h to obtain a casting solution with a solute mass fraction of 20-40%; S2, sending the film casting stock solution into the extruder for degassing, the extruder head pressure is 1.0-2.0MPa, the middle section temperature is 100-150℃, and the G / P inlet pump pressure is 2.0-5.0MPa; S3, the degassing film casting stock solution is filtered using a disc filter with a pore size of 10-20um; S4, casting the filtered film-casting stock solution through the slit die onto the casting roller to form a liquid film, while reducing the water content of the liquid film to 18-35%, and then reducing the water content to 5-15% through pre-drying, and then reducing the water content to 0.1-5% through heat treatment, and finally rolling up to obtain the anti-glare polyvinyl alcohol film.

11. The method for preparing the anti-glare polyvinyl alcohol film according to claim 10, characterized in that: In step S1, the solvent is water or dimethyl sulfoxide.

12. The method for preparing the anti-glare polyvinyl alcohol film according to claim 10, characterized in that: The anti-glare polyvinyl alcohol film has a light transmittance of ≥85% and a haze of 2-50%.

13. A polarizer, characterized in that: The intermediate film of the polarizer is a polarizing film made by iodine-dyed and stretched anti-glare polyvinyl alcohol film according to any one of claims 1 to 9, and the glossiness of the polarizing film at an angle of 60° is 30-70 GU.

Citation Information

Patent Citations

  • Antidazzle hard coating film, polarizing film using the film and image display apparatus

    CN101551474A

  • Composition for anti-glaring film

    CN102676004A

  • Preparation method of anti-glare antistatic sol for optical plastic surface

    CN104559352A

  • Polyvinyl alcohol optical film for polaroid and preparation method of polyvinyl alcohol optical film

    CN117946433A

  • Anti-dazzle film and preparation method thereof

    CN118006230A